Developing efficient scalar and vector intensity measures for IDA capacity estimation by incorporating elastic spectral shape information. - Vamvatsikos, Dimitrios
Scalar and vector intensity measures are developed for the efficient estimation of limit state capacities through incremental dynamic analysis (IDA) by exploiting the elastic spectral shape of individual records. IDA is a powerful analysis method that involves subjecting a structural model to several ground motion records, each scaled to multiple levels of intensity (measured by the intensity measure or IM), be defined and corresponding capacities can be calculated. When traditional IMs are used, such as the peak ground acceleration or the first mode spectral acceleration, the IM-values of the capacities can display large record to record variability, forcing the use of many records to achieve reliable results. By using single optimal spectral values as well as vectors and scalar combinations of them on three multistorey buildings significant dispersion reductions are realized. Furthermore, IDA is extended to vector IMs, resulting in intricate fractile DNA
Keywords: Performance-based earthquake engineering; Incremental dynamic analysis; Capacity; Intensity measure; Limit state; Non-linear.